If there are two sponsors for baptism one must be male and the other female: Canon 874 - Woestman, William H. (Roman replies and CLSA advisory opinions, 2006)
A couple is about to have their first born child and each wishes to request his or her sister to a godparent for the baby. They were told that the Code of Canon Law requires that when there are two sponsors for baptism one must be male and the other female, and that one could be a sponsor and the other a witness. However, they do not like this suggestion. Can a dispensation from this norm be granted? If so, by whom?